Dissemination of Religious Formation in The Fatwa of The Indonesian Ulema Council on Digital Da’wah Etichs - Rifky Nosah Pratama; Arifah Kholiana; Shakira Shakira; Fatma Kumala; Neska Fitri Noviyanti; Muhammad Alvian Fadhli Wibisono (TATHO: International Journal of Islamic Thought and Sciences, 2024)
Social religious problems triggered by the provocation of preachers in the digital media space are important problems to be addressed by all elements of society including the government. This qualitative research in the form of a literature review aims to identify the dimensions of religious formation in the Fatwa of the Indonesian Ulema Council (MUI) of East Java No. 6 of 2022. The theory of religiosity becomes the main theory of analysis in the discussion of this study. This data was obtained through documentation. Data were analysed through reduction, presentation and verification. This study shows the content of the formation of religiosity dimensions in the fatwa, such as da'wah recommendations that emphasise the practice of worship rituals, and attitudes to maintain harmony in social life amid social plurality. This research confirms the importance of disseminating holistic religious formation in digital da'wah materials. The limitations of this research have not examined the effectiveness of the fatwa in the community.